3D Environment Is Required In Vitro to Demonstrate Altered Bone Metabolism Characteristic for Type 2 Diabetics - Häussling, Victor (Int J Mol Sci, 2021)
A large British study, with almost 3000 patients, identified diabetes as main risk factor for delayed and nonunion fracture healing, the treatment of which causes large costs for the health system. In the past years, much progress has been made to treat common complications in diabetics. However, there is still a lack of advanced strategies to treat diabetic bone diseases. To develop such therapeutic strategies, mechanisms leading to massive bone alterations in diabetics have to be well understood. We herein describe an in vitro model displaying bone metabolism frequently observed in diabetics. The model is based on osteoblastic SaOS-2 cells, which in direct coculture, stimulate THP-1 cells to form osteoclasts. While in conventional 2D cocultures formation of mineralized matrix is decreased under pre-/diabetic conditions, formation of mineralized matrix is increased in 3D cocultures. Furthermore, we demonstrate a matrix stability of the 3D carrier that is decreased under pre-/diabetic conditions, resembling the in vivo situation in type 2 diabetics. In summary, our results show that a 3D environment is required in this in vitro model to mimic alterations in bone metabolism characteristic for pre-/diabetes. The ability to measure both osteoblast and osteoclast function, and their effect on mineralization and stability of the 3D carrier offers the possibility to use this model also for other purposes, e.g., drug screenings.